Phase Space Picture of Quantum Mechanics: Group Theoretical Approach (World Scientific Lecture Notes in Physics) - Y.S. Kim (World Scientific, 1991)
In this book, we disscuss about the physical consequences of the symmetritries of the Wigner function in phase space. this book is written for those scientists and students who wish to study the basic principles of the phase - space picture of quantum mechanics and physical applications of the wigner distribution fuctions. This book will also server a useful purpose for those who simply wish to study ythe physical applications of the Lorentz group.